Pedagogical Effectiveness of Creating Virtual Projects in Drawing Lessons - Raximova Gulsanam Hazrat qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This article examines the pedagogical effectiveness of integrating virtual projects into drawing lessons. The study highlights how virtual project-based learning enhances students’ creative and technical skills, encourages independent artistic activity, and fosters problem-solving abilities. Emphasis is placed on the use of digital tools, interactive software, and virtual modeling to enrich the learning process and improve educational outcomes.